2001
DOI: 10.1111/j.1469-7793.2001.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ongoing EMG by different classes of low-threshold mechanoreceptors in the human hand

Abstract: 2. Single cutaneous (n = 60), joint (n = 2) and muscle spindle (n = 34) afferents were recorded via tungsten microelectrodes inserted into the median and ulnar nerves at the wrist. Spiketriggered averaging was used to investigate synaptic coupling between these afferents and muscles acting on the digits. The activity of 37 % of FA I (7/19), 20 % of FA II (1/5) and 52 % of SA II afferents (11/21) evoked a reflex response. The discharge from muscle spindles, 15 SA I and two joint afferents did not modulate EMG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 63 publications
1
23
1
Order By: Relevance
“…Using the same approach, our laboratory has recently shown that in the hand, as in the leg, the synaptic strength of individual muscle spindle afferents is so weak that it cannot be identified using spike-triggered averaging of EMG (McNulty and Macefield 2001). However, we have also shown that individual low-threshold mechanoreceptors in the glabrous skin of the hand can cause reflex modulation of EMG of the muscles acting on the digits (McNulty and Macefield 2001;McNulty et al 1999).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using the same approach, our laboratory has recently shown that in the hand, as in the leg, the synaptic strength of individual muscle spindle afferents is so weak that it cannot be identified using spike-triggered averaging of EMG (McNulty and Macefield 2001). However, we have also shown that individual low-threshold mechanoreceptors in the glabrous skin of the hand can cause reflex modulation of EMG of the muscles acting on the digits (McNulty and Macefield 2001;McNulty et al 1999).…”
Section: Introductionmentioning
confidence: 81%
“…However, we have also shown that individual low-threshold mechanoreceptors in the glabrous skin of the hand can cause reflex modulation of EMG of the muscles acting on the digits (McNulty and Macefield 2001;McNulty et al 1999). Less than half of all the cutaneous mechanoreceptors exhibited any reflex coupling, with reflex coupling limited to the rapidly adapting type I (FA I), rapidly adapting type II (FA II), and slowly adapting type II (SA II) mechanoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly evident in women or men with smaller fingers where the more densely packed receptors have been suggested to improve acuity (Peters et al 2009). Second, Merkel receptors have the highest acuity (Phillips et al 1990) but are the only lowthreshold receptors in the glabrous skin of the hand for which a role in fine motor control could not be demonstrated (McNulty et al 1999;McNulty and Macefield 2001). This suggests that Merkel receptors may have stronger connections to the somatosensory cortex than other low-threshold mechanoreceptors and so provide a learnt attentional focus to cutaneous inputs (McNulty and Macefield 2001).…”
Section: Changes Across the Handmentioning
confidence: 99%
“…For example, in contrast to all other types of tactile afferents innervating the human glabrous skin, selective intraneural stimulation of single SA-II afferents does not evoke a percept (Torebjörk et al, 1987;Macefield et al, 1990). Likewise, impulses in SA-II afferents, including SA-IInail afferents, can influence automatically ongoing EMG in muscles acting on the digits through spinal pathways (McNulty et al, 1999;McNulty and Macefield, 2001). It is also possible that the tonic impulse activity in SA-IInail afferents, which is not consciously perceived, contribute to upholding digit representations in the central somatosensory system, which apparently requires continuous peripheral input (Kelahan and Doetsch, 1984;Tweedale, 1988, 1991).…”
Section: What Do the Sa-iinail Afferents Tell The Cns?mentioning
confidence: 99%